Zaburzenia karmienia u dzieci - codzienny problem każdego pediatry - Krogulska, Aneta; Gaweł, Ewelina (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Feeding disorders occur in some infants and younger children. These disorders are not easy to solve for parents and pediatricians. In this paper, we present the classification, diagnostic, and treatment of feeding disorders in children.